Phage phiZ98: A novel tri-segmented dsRNA cystovirus for controlling Pseudomonas strains with defective lipopolysaccharides in foods. (December 2022) - Li, Donghang; Li, Yueying; Li, Peize; Han, Qingzhu; Zhang, Tian; Yang, Baopeng; Wu, Weihui; Yang, Hongjiang
Graphical abstract: Highlights: Identification and characterization of a novel Cystovirus phiZ98. PhiZ98 can lyse P. aeruginosa and P. fluorescens strains with defective LPS. PhiZ98 can effectively inhibit biofilm formation and remove mature biofilm. PhiZ98 can effectively control bacterial growth in milk and ready-to-eat beef. PhiZ98 can effectively reduce phage-resistant mutants from K8 application in milk. Abstract: Many Pseudomonas phages recognize lipopolysaccharides (LPS) as the receptor for infection. LPS defective mutants are often recovered from phage treatments, possibly causing the failure of phage applications. In this work, we isolated a lytic Pseudomonas phage, phiZ98, that can specifically lyse LPS defective strains of the genus Pseudomonas . Transmission electron microscopy (TEM) showed that phiZ98 particles were enveloped in a layer of membrane-like structure. Genomic analysis revealed that the phage has a genome of tri-segmented double-stranded RNA molecules of 6627 bp, 3769 bp, and 3075 bp, respectively. The results indicated that phage phiZ98 was the nineth member of the genus Cystovirus. The phiZ98 genome encoded 12 putative proteins with predicted functions and 15 hypothetical proteins. Mass spectrum analysis further identified 11 proteins present in the virions. Antibacterial activity assays showed that phage phiZ98 significantly inhibited cell growth, reduced biofilm formation, and removed mature biofilm. Moreover, phage phiZ98 can significantly control the growth of the host bacterial cells in sterilized milk or canned corned beef. In combination with phage K8 which used LPS as the receptor, phiZ98 can significantly reduce the phage-resistant mutants generated from the K8 treatment in milk. Taken together, the dsRNA phage phiZ98 could be an effective scavenger in removing phage-resistant mutants with defective LPS in cocktail applications.